Campus Buddy - Choudhary, Anamika Nupur (Kansas State University, 2017)
New to K-State??? No worries!!! This app will be your first friend and help you with everything you may need. Every new incoming student to K-State has to do a set of mandatory activities before they start their classes. Many times they use a pamphlet or word of mouth by students or faculty around, on what to do and whom to visit. But, this information may not be reliable or could have been expired/updated, and students miss on certain crucial things which delays their work. The same follows with various events organized by the college to welcome new students. This app will be a solution for all these problems. It will provide students with all the details they need before they actually become familiar with the school and even after that. Each student gets to see the To-Do's which are a set of mandatory activities, he/she has to do before they enroll for the classes and also, he can know about various events happening around the university. Students can also suggest new events if they are not already updated in the events list. All these activities are monitored and controlled by the Admin.
Keywords: Your first buddy at K-State; Spring MVC; AngularJS validation; Helps you track mandatory to-do's and events list; Web technologies